Faktor Pembelajaran Pendidikan Islam dalam Kurikulum Merdeka - Sembiring, Yana Juhri Artika; Dahlan, zaini (Jurnal Generasi Tarbiyah: Jurnal Pendidikan Islam, 2025)
This research aims to explore the factors that influence Islamic Education learning in the Independent Curriculum Context. The research method used is this research approach will use literature analysis as the main methodology. The initial step involves identifying related literature through academic databases such as Google Scholar, JSTOR, and ProQuest using keywords such as "Islamic Education", "Independent Curriculum", and "Learning Factors". It is hoped that this research can provide in-depth insight into the effectiveness of Islamic Education learning within the Independent Curriculum framework and provide recommendations for further development.